LACK OF AN ENABLING ENVIRONMENT FOR CULTURAL ACTIVISM (ЕтноАнтропоЗум/EthnoAnthropoZoom, 2011)
The lack of cultural activities of good quality from the beginning of the transition in Macedonia began to permeate with the appearance of formally or informally registered associations of citizens, active in the field of culture, aiming at creating constructive systems of values. The values they created, have educated several generations of young people raised in the period of transition of society, but they failed to win their place in the newly created market society. Today, when Macedonia attempts to officially put an endto the transition period, it seems that the neoliberal policies trampled over the civil initiatives in the area of culture and left no room to fill ne cultural needs of all civil groups.
Keywords: cultural policy; culture